Effect of type of fried foods on the quality of frying oil / Nor Fishah Mohamad Nor - Mohamad Nor, Nor Fishah (Faculty of Applied Sciences, 2012)
This study was conducted to determine the effect of types of fried food on the physicochemical properties of palm oil. Determinations of peroxide value, Iodine value and TBA value of frying oil were used to study the stability of palm oil, while polar compounds, polymer compounds, fatty acid contents, free fatty acid (%FFA), colour and viscosity were conducted to determine the quality and frying performance of the oils. The results obtained showed that fresh potatoes was the food that showed the highest content in %FFA, PV, TBA, and polymer compounds in the fried palm oil, whereas tapioca chips showed the lowest values in %FFA, PV, TBA, polar compounds, polymer compounds, and IV in the fried palm oil. All foods (tapioca chips, French fries and fresh potatoes) showed decreasing %SFA and increasing %MUFA while only fresh potatoes and French fries showed decreasing %PUFA in the fried palm oil. The results of this study indicated that frying oil that was used to fry foods increased in %FFA, TBA, polar compounds, polymer compounds, colour (a*= redness and b*= yellowness), and viscosity but for PV, the rate of increase was not constant as frying progressed.